Magnetic-based multi-layer microparticles for endothelial progenitor cell isolation, enrichment, and detachment - Wadajkar, Aniket S. (2013)
Although endothelial progenitor cells (EPCs) are useful in many applications including cell-based therapies, their use is still limited due to issues associated with cell culture techniques like a low isolation efficiency, use of harmful proteolytic enzymes in cell cultures, and difficulty in ex vivo expansion. Here, we report a tool to simultaneously isolate, enrich, and detach EPCs without the use of harmful chemicals. In particular, we developed magnetic-based multi-layer microparticles (MLMPs) that (1) magnetically isolate EPCs via anti-CD34 antibodies to avoid the use of Ficoll and harsh shear forces; (2) provide a 3D surface for cell attachment and growth; (3) produce sequential releases of growth factors (GFs) to enrich ex vivo expansion of cells; and (4) detach cells without using trypsin. MLMPs were successful in isolating EPCs from a cell suspension and provided a sequential release of GFs for EPC proliferation and differentiation. The cell enrichment profiles indicated steady cell growth on MLMPs in comparison to commercial Cytodex3 microbeads. Further, the cells were detached from MLMPs by lowering the temperature below 32 °C. Results indicate that the MLMPs have potential to be an effective tool towards efficient cell isolation, fast expansion, and non-chemical detachment.